The Health and Well-being of Service User and Carer Educators: a Narrative Enquiry into the Impact of Involvement in Healthcare Education. (2014) - Rhodes, Christine; Hardy, Joan; Padgett, Kath; Symons, Jools; Tate, Joannie; Thornton, Susan
No abstract available